Analysis of current evidence on post-operative pain for endodontic treatment: literature review (Research, Society and Development, 2021)
Postoperative pain after endodontic treatment has a multifactorial origin and can affect the patient's quality of life. A variety of techniques and combinations can achieve pain control during endodontic procedures. Being aware of these factors guides the dentist in his ability to increase patient confidence, conduct treatment according to risk factors for pain, and take steps to reduce symptoms. Thus, the objective of this study was to analyze the evidence currently available on the topic of postoperative pain to endodontic treatment. For its realization, a survey was carried out on the PubMed platform and systematic review articles published between 2016 and 2021 were included. The results of this study showed that the administration of preoperative medication, maintenance of apical patency, agitation of the irrigating substance with automated devices and the use of intracanal cryotherapy are favorable in preventing and/or reducing postoperative symptoms. However, new well-designed randomized clinical trials are needed to better clarify some factors related to algesia after endodontic treatment.